The Relationship Between Self-Efficacy and Empathy with Resilience in Bala Rescue Volunteers in Disaster Preparedness - Ady Waluya; Johan Budhiana; Nunung Liawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Earthquakes are sudden natural events caused by the movement of tectonic and volcanic plates. According to data from the National Disaster Management Agency (BNPB) from 2019 to 2023, there have been 3,855 earthquakes in Indonesia. Therefore, disaster volunteers are required to have high resilience. There are various factors that contribute to resilience, including self-efficacy and empathy. To determine the relationship between self-efficacy and empathy with resilience in Jaga Bala Rescue volunteers in dealing with earthquakes in Cianjur Regency. This cross-sectional study involved 62 Jaga Bala Rescue volunteers in Cianjur Regency, who were selected using total sampling. Data were collected using validated and reliable questionnaires, with a validity index p-value < 0.05 and reliability > 0.70, namely the GSES, Empathy based on the Likert scale, and CD-RISC 20. Data were analyzed using Somers' d test to identify the relationship between variables. Results: The results of the analysis showed a significant relationship between self-efficacy (p = < 0.001) and empathy (p = 0.009) with the resilience of Jaga Bala Rescue volunteers. There was a significant relationship between self-efficacy and empathy with resilience in Jaga Bala Rescue volunteers in their preparedness for earthquakes in Cianjur Regency.